Apakah Inklusi Keuangan dan Kematangan Digital Mengoptimalkan Pengambilan Risiko Bank? - Kurniawan, Agung; Setyowati, Servatia Mayang; Mortadza, Noor Shazreen (Politeknik Ganesha Medan, 2024)
This study aims to investigate the effectiveness of the implementation of digital financial inclusion and banking digital maturity on the tendency of risk-taking behavior in Indonesian banks. This study highlights the risk-taking behavior that is proxied in default risk, leverage risk, and portfolio risk. This study uses secondary data to conduct a comprehensive content analysis of Indonesian banking companies from 2013 to 2023. Based on the availability of data, 66 banks in Indonesia were selected as the object of the empirical study. The test in this study uses the ordinary least squares model to test the hypothesis, and the feasible generalized least squares model to test the durability of the model used. The findings of this study reveal that the implementation of digital financial inclusion and banking digital maturity have a significant impact on banks' risk-taking behavior. The implementation of appropriate digital financial inclusion can encourage banks to mitigate banks risk-taking behavior, and increasing the digital maturity of banks can encourage banks to be more daring to take risks. These findings have been reinforced with robustness testing, which shows consistent results using different testing models.